The perceptions of Turkish students against scientists and the emotions of scientists in the post-pandemic - Turkmen, Hakan; Koseoglu, Pelin (Asian Journal of Contemporary Education, 2023)
Today’s students are expected to think like scientists. Every student has a different life and they learn in different ways. We need to understand how students view scientists and what their perceptions of them are in order to make these expectations a reality. This study aims to investigate the perceptions that Turkish secondary school students have of scientists and show how these perceptions have changed in the wake of the pandemic particularly with regard to the emotions of scientists. This research is survey research. The Draw a Scientist Test Checklist (DAST-C) was used as the data collection and analysis tool for the research. In the emotion dimension of this study, emotions in the Plutchik Emotion Model were based on the data collection tool. Descriptive statistics were used to analyse the data. Students’ perceptions of scientists in this study show a fall in the rates of the standards that constitute the stereotypical image. In the findings of the study, it was seen that the scientist was generally young and female. This shows that recent developments have changed students’ perceptions. It is clearly seen that the pandemic has changed the minds of scientists and students.